Use of Fermentation of Rice Wash Water (Oriza Sativa) As Liquid Organic Fertilizer (POC) (Fakultas Teknik, Universitas Brawijaya, 2025)
Household waste, including residues from daily activities, can negatively impact the environment if not properly managed. This study focuses on household waste management in RT 03 RW 01 Desa Ngadilangkung, Kecamatan Kepanjen, Kabupaten Malang, with the aim of raising awareness and knowledge among the community about the benefits of rice washing water. The methods used include primary surveys through observations and interviews with village officials, the head of RW, the head of RT, and the community. The survey results indicate that most households have not optimally utilized rice washing water, with only 6% of households engaging in processing and 94% not recycling. Socialization efforts were conducted to educate the community on the production of liquid organic fertilizer (POC) from rice washing water, which is expected to improve waste management and more effectively utilize household waste. The outreach results indicate a significant potential for the application of POC in the village, although there remains a need for further education on waste management.